บทบาทของครูและผู้ปกครองในการส่งเสริมจริยธรรมของนักเรียน : พหุกรณีศึกษา - สุสรรค์ ไชโยรักษ์ (จุฬาลงกรณ์มหาวิทยาลัย, 2006)
The objectives of this research were: 1) to study the role of teachers and parents in enhancing ethics in students. 2) to compare the role of teachers and parents in enhancing students ethics in the enhancing ethics school with the normal school 3) to compare ethics of students who received the enhancement ethics from the role of teachers and parents in the enhancing ethics school and normal school 4) to study the supportive factors and obstacle factors from teachers and parents in enhancing ethics in students. The qualitative methods in multi-case study was employed. One case study was the enhancing ethics school and the other was the normal school. Data were collected for a period of 5 months by documentary analysis, observation, interviews and focus group. The results of the research indicated: 1. The role of teachers in enhancing ethics consisted of 12 methods; 1) being good example 2) creating an atmosphere 3) inspiring 4) the quality of love and compassion 5) practice suitable students behavior 6) practice students discovery truth 7) practice students peaceful mind 8) practice students love and compassion 9) practice students non-violence 10) teaching using the experience of others 11) being love and compassion 12) enhancing in discipline. The role of parents in enhancing ethics in students consisting of 9 methods; 1) enhancing the physical development 2) creating an atmosphere 3) creating loving relationship 4) being a good example 5) creating discipline 6) teaching analytical thinking 7) building up trust 8) inspiring 9) preventing negative behaviors 2. The role of teachers in enhancing ethics in the enhancing ethics school were similar to normal school in 4 role; 1) being good example 2) creating an atmosphere 3) inspiring 4) teaching using the experience of others. The role of parents of students in 2 schools is similar, that is building of loving relationship, setting up good examples and creating discipline. 3. Students in a school enhancing ethics have the ethics level 62.5% for self that requires self imprvement, 25% for the close up person and 12.5% for the society whereas in the normal school 75% for self improvements, 25% for close up person and none for the society. 4. The supportive factors forthe role of teachers were 1) management 2) commitment to create good people 3) creating an atmosphere 4) teacher s character and ability 5) instruction 6) variety of cultures 7) budget and the obstacle factors were 1) lack of good publicity 2) parents attitude and participation 3) external media 4) lack of updated knowledge. The supportive factors for the role of parents were 1) the characteristics of occupation 2) learning from experience of the society and the obstacle factors were 1) time management 2) group of friends.